Penerapan Cooperative Learning Tipe STAD, Guided Inquiry dan Problem Based Learning dalam Perspektif Kristen [The Implementation of STAD-Type Cooperative Learning, Guided Inquiry and Problem Based Learning in Christian Perspective] - Sianipar, Lanny; Tampubolon, Meliana Rodearni; Polak, Aurelia Friscilla; SUWU, Selvi Esther; Chrismastianto, Imanuel Adhitya Wulanata (Universitas Pelita Harapan, 2025)
School and learning are inseparable. Meaningful learning looks at several aspects in its implementation, such as the school environment, classroom management, student character to the model or lesson method used. Teachers in this case play a role as agents of reconciliation who can introduce God to their students in the classroom, this can also start from the teacher choosing a learning model. One of the learning models that can be chosen is cooperative learning which uses a model of cooperation in learning. There are various kinds of cooperative learning models, but in this study, there are three discussed. Thus, the purpose of this research is to find out the cooperative learning type STAD, Guided Inquiry and Problem based Learning in Christian perspective. With the literature review method, the results of this study are that the use of the STAD learning model has a positive impact on students, and by the philosophy of Christian education emphasizes the importance of human relations with others as the image and likeness of God. The application of the guided inquiry learning model requires the active involvement of a teacher to guide students both cognitive, social, emotional, and spiritual in learning. Project-based learning in its implementation is expected to be able to direct students to holistic growth in accordance with the role of Christian teachers in the discipleship process.